A study of lifestyle modifications with and without metformin in prediabetic subjects - Asha Basavareddy; Narayana Sarala; Venkatarathnamma P Nanjappa; Sumathi M Eshwarappa (Journal of Diabetology, 2022)
Purpose: Prediabetes is a stage in the natural history of impaired glucose metabolism rather than as a distinctive clinical entity. The primary objective was to compare the effect of lifestyle modifications (LSMs) with and without metformin in prolonging the onset of diabetes mellitus in prediabetics. Materials and Methods: This study is an open label, parallel group comparative study conducted from 2016 to 2020. One hundred and four prediabetic subjects were assigned to two groups: group I (51) LSM and group II (53) metformin 500 mg along with LSM. Baseline investigations included fasting blood sugar (FBS), post-prandial blood sugar (PPBS), HbA1c, and lipid profile, followed up for 12 months. Results: The baseline parameters were comparable between the groups. In both the groups, there was a significant reduction in abdominal circumference, total cholesterol, triglycerides, low-density lipoprotein, FBS, PPBS, and HbA1c between baseline and 1 year. There was no significant difference between groups I and II in reduction of all the above-mentioned parameters. The outcomes of prediabetic subjects after 1 year of treatment in both the groups were comparable. Only one (2.1%) subject had more than 126 mmHg FBS in the LSM group. The adverse effects observed were dizziness, nausea, flatulence, myalgia, abdominal pain, and heart burn, which were mild to moderate in intensity and in most patients it subsided with time. Conclusion: LSM alone was equivalent to LSM along with metformin in effective control of blood sugars. Lipid profile and weight may be significantly reduced.